Artist Spotlight: Arthur Taussig - Taussig, Arthur (Cornfield Review, 2021)
This special spotlight on California multimedia artist and musician Arthur Taussig includes the following sections: • "Introdction to H. Arthur Taussig (Drew Niemi & Jerome F. Shapiro, curators) • "More Taussig Online" (links to various performances, artwork, and interviews) • "Photographic Art" (A sampling of Taussig's visual artwork) • "A Brief History of Contact" (excerpt from a science-fiction novel by Taussig)